2004
DOI: 10.1007/bf02872387
|View full text |Cite
|
Sign up to set email alerts
|

pre-operative serum potassium levels and peri-operative outcomes in patients undergoing cardiac surgery

Abstract: Although potassium is critical for normal electro physiology, the associations between pre-operative serum potassium level and peri-operative adverse events such as arrhythmias in cardiac surgery have not been examined in detail.The objective of this study was to determine the prevalence of abnormal pre-operative serum potassium levels and whether such levels were associated with adverse peri-operative events in 50 patients undergoing coronary artery bypass grafting. Intra-operative and post-operative arrhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Campbell et al [37] investigated the impact of maintaining serum potassium ≥ 3.6 mmol/L in comparison to ≥4.5 mmol/L on the incidence of NOAF after coronary artery bypass grafting, but the authors did not publish the results. In another study [36], preoperative hypokalemia (<3.5 mmol/L) was associated with AF. None of the abovementioned data concerned patients with AMI.…”
Section: Clinical Laboratory and Echocardiographic Parametersmentioning
confidence: 90%
See 1 more Smart Citation
“…Campbell et al [37] investigated the impact of maintaining serum potassium ≥ 3.6 mmol/L in comparison to ≥4.5 mmol/L on the incidence of NOAF after coronary artery bypass grafting, but the authors did not publish the results. In another study [36], preoperative hypokalemia (<3.5 mmol/L) was associated with AF. None of the abovementioned data concerned patients with AMI.…”
Section: Clinical Laboratory and Echocardiographic Parametersmentioning
confidence: 90%
“…One of the well-known parameters connected to AF development in the general population is low potassium level in serum [35][36][37][38]. In the Rotterdam Study [35], potassium below 3.50 mmol/L was associated with a higher risk of this arrhythmia.…”
Section: Clinical Laboratory and Echocardiographic Parametersmentioning
confidence: 99%
“…Goyal et al reported that serum potassium values of less than 3.5 or more than 5.0 mEq/L were associated with a high adverse cardiac event and mortality rate in patients with acute myocardial infarction [17]. Hypokalemia was also found to be a predictor of serious peri- and postoperative arrhythmias [18]. As shown in Figures 1A and 2 A, an increase in the number of repeat critical value s for serum potassium was closely related to an increase in mortality (from 4.5% to 9.9% and 10.2%) with a decrease in healing rating (from 17.7% to 10.7% and 7.7%).…”
Section: Discussionmentioning
confidence: 99%
“…NOAF and AF groups had the highest WBC on admission, and the NOAF group had a peak WBC during the second day of in-hospital treatment ( Table 3 , Figure 3 ). Low serum potassium level is the next well-known characteristic linked to the development of AF in the general population [ 23 , 32 , 33 , 34 ]. In our previous study, potassium levels below 4.2 mmol/L were found to be crucial in revealing the NOAF probability [ 9 ].…”
Section: Discussionmentioning
confidence: 99%